(3JMQjQ cJGH GdGNJjGQ ef cJGH CHj YeQh GdcTj aj GdQLGds - (3GdYGedj, GdTGej, CHh efUhQ, GHf GdTgjO GdKGfj, GdMSf Hf Rjf GdOjf Hf Ydj Hf CMeO, J (B1011 (3g`s ((3eMeO Hf WGgQ GdSeGhjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3hGdHGYK dj Ydi gPG Gfj de CXaQ HcJGH GdSjO QMeg Gddg HfSNI ZjQ fSNI GdCUd GdJj CZdHgG HNW GdeUfa (B... (3hQCjJ HYO GdJCed Cf Gdege efg gh JMQjQ cJGH GdGNJjGQ(B...s
(3BNQgG (B:s
.. (3MOKfj CHh GdMSf GMeO Hf MGJe Hf eGghjI bGd (B: (3CJjJ Edjg (B- (3jYfj CHG GdMSf GdKGdK (B- (3Ydjg GdSdGe CSCdg Yef BNP eYGde Ojfj ? (B... (3Ef TGA Gddg JYGdis
(3JHUQI GdYfhGf (B:s
(3cJGH GdGNJjGQ ef cJGH CHj YeQh GdcTj aj GdQLGd d LeGd GdOjf CMeO Hf WGhS GdMSjfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\192s
(3GdPQjYI (B3 - 211( 1390 )s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs